Assessment of HIV knowledge among university students using the HIV-KQ-18 scale: A cross-sectional study - Talwar, Prashanth; Rahman, Mohd Fadzil B Abd (South East Asia Journal of Public Health, 2015)
Globally, the spread of HIV/AIDS has become a major health concern due to its pandemic proportions. Although people of any age are vulnerable to HIV, the younger populace are more at risk of becoming infected due to their lifestyle choices. The aim of the study was to assess the level of HIV-related knowledge among undergraduate university students using the HIV-KQ-18 scale, and thereby determine a relationship between the selected demographic variables and HIV knowledge. A cross-sectional study was conducted among 405 students enrolled in a Malaysian University, using a self-administered questionnaire. The HIV-KQ-18 scale was used to measure participants basic knowledge about HIV, modes of its transmission and prevention. The study indicated that majority of the students (64%) had adequate HIV-related knowledge. Accounting for socio-demographics, it was noted that lower age group, male and Faculty of Science students were the variables associated with higher HIV knowledge scores. Multiple regression analysis predicted three variables namely gender, faculty and relationship status as being significantly associated with knowledge. Essentially, findings from the study indicate significant differences in the gendered knowledge of HIV, demonstrating a need to conduct more gender-based studies in different settings. Furthermore, it is recommended that age and gender specific educational interventions strategies could be implemented to address misconceptions about HIV, modes of its transmission and effective prevention. South East Asia Journal of Public Health Vol.5(1) 2015: 33-38